2017
DOI: 10.1039/c7ra07421b
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ambient conditions on the evolution of wettability properties of an IR-, ns-laser textured aluminium alloy

Abstract: aMicro cell structures of different sizes were patterned using a nanosecond near-infrared laser source on Al2024 aluminium alloy plates with 2 mm thickness. The influence of laser parameters on the shape and size of the produced patterns were studied together with the evolution of wettability properties over time for different storage conditions. Samples were found to be superhydrophobic from a single step laser patterning, requiring no further treatment. Exposure to ambient air was shown to be a key factor in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(67 citation statements)
references
References 46 publications
4
61
0
Order By: Relevance
“…The overlap, O, between two consecutive circular pulses can be approximated by the geometrical equation [34]:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overlap, O, between two consecutive circular pulses can be approximated by the geometrical equation [34]:…”
Section: Methodsmentioning
confidence: 99%
“…Modification of surface chemistry together with activation and adsorption of hydrocarbon molecules by the resulting organic layer could explain this phenomenon [27,42,44]. The storage condition of the laser-textured samples also plays an important role in the aging process [34].…”
Section: Surface Functionalitymentioning
confidence: 99%
“…The material removal takes place locally at the zone where the laser beam is interacting with the substrate and also causes a limited chemical surface modification. [ 27 ] From an industrial point of view, S/US pulsed laser technologies are very flexible and allow to treat a wide range of materials as long as the substrate absorbs the used laser wavelength (i.e., infrared (IR) and visible (VIS) for metals [ 28,29 ] and ultraviolet (UV) for polymers [ 30 ] ). In addition, the scale‐up of such technologies for industrial applications has been already demonstrated in several cases.…”
Section: Introductionmentioning
confidence: 99%
“…This route to fabricate micropatterns, nanoripples or dual-scale structures has been investigated by many researchers. However, the evolution of their respective surface chemistry in ambient air or storage conditions is less studied while it is of prime importance in retaining the attractive surface functionality for as long as possible [9][10][11]. At the same time another indirect route for enhancing the hydrophobic properties of chemically stable polymers is gaining importance, especially through the use of well-established replication processes to transfer laser-fabricated surface textures/structures on tooling inserts onto thermoplastic parts [12][13][14].…”
Section: Introductionmentioning
confidence: 99%